Pemanfaatan aplikasi canva sebagai media pembelajaran untuk meningkatkan minat belajar siswa Kelas X-4 SMA Negeri 1 Tondano - Pangalila, Theodorus; Paka, Nuriska; Pombaile, Ervina; Abdul, Apriyanti; Sampel, Ferry Lourens (Academy of Education Journal, 2024)
This research was conducted with the aim of finding out the use of the Canva Application as a Learning Media to increase the Learning Interest of Class X-4 Students at SMA Negeri 1 Tondano. This research method is qualitative and to obtain results from the research, it was carried out by directly observing students in class X-4 and trying to use the Canva application technology to see whether it could increase students' interest in learning. Learning media are tools that can help the teaching and learning process. Material can be more easily transferred and absorbed by students. One of the media used is media that is able to attract students' interest in understanding the lesson, namely the Canva application. Canva is a design tool that uses the internet network. Everyone can use Canva with the interesting features provided in the application. With the Canva application, it is hoped that it can help students and teachers in the learning process.